2004
DOI: 10.1063/1.1711811
|View full text |Cite
|
Sign up to set email alerts
|

Converged quantum calculations of HO2 bound states and resonances for J=6 and 10

Abstract: Accurate quantum calculation of the bound and resonant rovibrational states of Li − ( H 2 ) J. Chem. Phys. 122, 124318 (2005) Bound and resonance states of HO 2 are calculated quantum mechanically using both the Lanczos homogeneous filter diagonalization method and the real Chebyshev filter diagonalization method for nonzero total angular momentum Jϭ6 and 10, using a parallel computing strategy. For bound states, agreement between the two methods is quite satisfactory; for resonances, while the energies are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 73 publications
0
31
0
Order By: Relevance
“…It presents a big challenge for quantum scattering calculations because of its deep well and the heavy masses ͑only one hydrogen atom and two oxygen atoms͒ involved. As a consequence, several studies concerning the rate coefficients, 2-6 reaction dynamics, [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] and the reaction intermediate [25][26][27][28][29][30][31][32][33] are available in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…It presents a big challenge for quantum scattering calculations because of its deep well and the heavy masses ͑only one hydrogen atom and two oxygen atoms͒ involved. As a consequence, several studies concerning the rate coefficients, 2-6 reaction dynamics, [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] and the reaction intermediate [25][26][27][28][29][30][31][32][33] are available in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…revealed an important role of Coriolis coupling in a time-dependent wave packet study of the OþNH or NþOH reaction, a system with double deep well. Zhang and Smith 21,22 have found that the Coriolis coupling becomes more important as J increases and the helicity conserving approximation is not a good one for the HO 2 resonance states…”
Section: Oþh 2 Reactionmentioning
confidence: 98%
“…The latter depends on the two rotational constants, A and B, and on the rotational state labels, (J, K). For a highly prolate symmetric rotor such as SO 2 , A B [43,44,45,46,47,48].…”
Section: J-shiftingmentioning
confidence: 99%